NIR-II emissive multifunctional AIEgen with single laser-activated synergistic photodynamic/photothermal therapy of cancers and pathogens. (November 2020) - Xu, Yuling; Zhang, Yi; Li, Jun; An, Jusung; Li, Chonglu; Bai, Suya; Sharma, Amit; Deng, Ganzhen; Kim, Jong Seung; Sun, Yao
Abstract: Despite the wide application of the traditional NIR-I phototheranostic platforms in basic research and clinical studies, problems such as tissue scattering, auto-fluorescence combined with aggregation caused quenching hamper precise image-guided phototherapy. Herein, we developed a multifunctional NIR-II phototheranostic platform using a novel AIE-based dye (ZSY-TPE ) for single laser-activated imaging-guided combined photothermal and photodynamic therapies of tumors and pathogens. As confirmed through in vivo studies, the ZSY-TPE dots displayed precise and efficient high-performance NIR-II imaging-guided combination phototherapy against 4T1 tumor as well as S. aureus-infected mice models without any noticeable side effects. The current study demonstrates ZSY-TPE as a powerful phototheranostic platform for precise NIR-II fluorescence/PA imaging and synergistic photodynamic/photothermal therapy of tumors and bacterial infections. Graphical abstract: Image 1